2014
DOI: 10.1016/j.surg.2013.12.009
|View full text |Cite
|
Sign up to set email alerts
|

For-profit hospital ownership status and use of brachytherapy after breast-conserving surgery

Abstract: BACKGROUND Little is known about the relation between surgical care for breast cancer at for-profit hospitals and subsequent use of adjuvant radiation therapy (RT). Among Medicare beneficiaries, we examined whether hospital ownership status is associated with the use of breast brachytherapy – a newer and more expensive modality – as well as overall RT. METHODS We conducted a retrospective study of female Medicare beneficiaries receiving breast-conserving surgery for invasive breast cancer in 2008 and 2009. W… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
2
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 44 publications
1
2
1
Order By: Relevance
“…In hospitals with for-profit ownership, patients reported significantly more social support from nurses than in public hospitals. However, on the basis of our data, we cannot provide explanations for this result, and results from previous studies concerning associations between hospital ownership and patient care have been inconsistent [23,35]. The fact that significant results are found for ownership only in the third model might be ascribed to the high variance explanation achieved by adding the variables describing process organization.…”
Section: Interpretation Within the Context Of The Wider Literaturecontrasting
confidence: 80%
“…In hospitals with for-profit ownership, patients reported significantly more social support from nurses than in public hospitals. However, on the basis of our data, we cannot provide explanations for this result, and results from previous studies concerning associations between hospital ownership and patient care have been inconsistent [23,35]. The fact that significant results are found for ownership only in the third model might be ascribed to the high variance explanation achieved by adding the variables describing process organization.…”
Section: Interpretation Within the Context Of The Wider Literaturecontrasting
confidence: 80%
“…Finally, more for‐profit hospitals explained the shorter treatment delays in Kentucky. Recent research has found for‐profit hospitals adopting newer, costly treatments for breast cancers . This finding is consistent with previous research showing for‐profit facilities respond to changes in demand and technology faster than other hospitals.…”
Section: Discussionsupporting
confidence: 88%
“…We included hospital referral region-level two year rate of mammogram among female Medicare enrollees age 67–69, divided in quartiles, as this has been shown previously to be associated with receipt of brachytherapy. (21)…”
Section: Methodsmentioning
confidence: 99%